2009
DOI: 10.1177/229255030901700313
|View full text |Cite
|
Sign up to set email alerts
|

Use of botulinum toxin in cheiloplasty: A new method to decrease tension

Abstract: Objective To determine if the use of botulinum toxin during cheiloplasty could help in the management of tension at the surgical wound level. Interventions Five children younger than six months of age, who were born with complete cleft lip and palate, were treated with a dose of 10 units of botulinum toxin injected into the upper lip during surgery. Before the surgery, an electromyographic study was carried out on the patients' upper lips. A Millard-type cheiloplasty was performed and 10 days later, a second e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…11 Nine years after the work of Revera et al, Galarraga confirmed the inhibition of the orbicularis oris muscle by using BTX during cleft lip repair by the EMG. 12 The results of our study, presence of less difference between the cleft and the non-cleft sides in the BTX group came in agreement with the previous conclusion that the orbicularis oris muscle increased activity correlates to shorter lip and inhibiting this activity may prevent the complication of shorter incompetent lip.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…11 Nine years after the work of Revera et al, Galarraga confirmed the inhibition of the orbicularis oris muscle by using BTX during cleft lip repair by the EMG. 12 The results of our study, presence of less difference between the cleft and the non-cleft sides in the BTX group came in agreement with the previous conclusion that the orbicularis oris muscle increased activity correlates to shorter lip and inhibiting this activity may prevent the complication of shorter incompetent lip.…”
Section: Discussionsupporting
confidence: 92%
“…Although Chang et al used the BTX at the end of the cheiloplast surgery. Galárraga 12 also had a different opinion as he considered the intraoperative administration of BTX-A is appropriate because the children frequently suffer from upper respiratory tract infections that often delay the surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…BTX has been used to treat hypertrophic scars (HS) and keloids in a number of studies [8], [9], [10], [11], [12], [13], [14] and also was successfully used in scar prevention [14], [15], [16], [17], [18], [19], [20], [21]. Only a small number of available studies were made as randomized controlled trials with the efficacy of BTX compared to placebo (saline solution) or steroids, and those studies differ for the amount of BTX used ranging from 1.5 to 5 IU every cm2 and for the frequency of treatment ranging from a single treatment to multiple treatments done every month or even with longer intervals, but all gave positive results.…”
Section: Resultsmentioning
confidence: 99%
“…Although the scars were reported to be satisfactory, the study lacked any subjective or objective scar assessment tools to support such a conclusion. Galarraga [21] showed that intraoperative BTA injections significantly reduced orbicularis oris activity when measured by electromyography. An electromyographic study was conducted in the upper lip of five infants (aged < 6 months) before surgery.…”
Section: Bta In Cleft Lip Repairmentioning
confidence: 99%